1991
DOI: 10.1111/j.1365-2621.1991.tb05344.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Packaging on Physical and Sensory Characteristics of Ground Pork in Long‐term Frozen Storage

Abstract: Effects of packaging materials on water-holding capacity (WI-Q thaw and cook losses, TBA value, moisture and fat content, and sensory characteristics of ground pork held in frozen storage for 13, 26, or 39 wk were examined. Moisture and juiciness decreased and total losses (thaw + cook) increased over time regardless of packaging. WHC decreased most in PVC-packaged pork (fresh = 0.53,39 wk = 0.17) and least for vacuum-packaged pork (39.wk = 0.25). After 39 wk TBA values were highest for PVC-packaged (2.98) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 13 publications
3
12
1
Order By: Relevance
“…salt content, protein level) and processing conditions (e.g. storage temperature and time) (Bhattacharya, Hanna, & Mandigo, 1988;Brewer & Harbers, 1991;Jiménez-Colmenero et al, 2003;Serrano, Cofrades, & Jiménez-Colmenero, 2006). Bhattacharya et al (1988) and Brewer and Harbers (1991) found similar weight losses to the ones in this study in salt-free ground meat, which were greater than in samples with normal salt content as reported by other authors (Jiménez-Colmenero et al, 2003;Serrano et al, 2006).…”
Section: Thawing and Cooking Lossessupporting
confidence: 87%
See 2 more Smart Citations
“…salt content, protein level) and processing conditions (e.g. storage temperature and time) (Bhattacharya, Hanna, & Mandigo, 1988;Brewer & Harbers, 1991;Jiménez-Colmenero et al, 2003;Serrano, Cofrades, & Jiménez-Colmenero, 2006). Bhattacharya et al (1988) and Brewer and Harbers (1991) found similar weight losses to the ones in this study in salt-free ground meat, which were greater than in samples with normal salt content as reported by other authors (Jiménez-Colmenero et al, 2003;Serrano et al, 2006).…”
Section: Thawing and Cooking Lossessupporting
confidence: 87%
“…CL increased (P < 0.05) up to day 18 and then decreased until day 152, when the values were the same as at the beginning. This cannot be explained by the fact that frozen storage causes protein denaturation, which results in loss of protein solubility, causing increases in thaw drip during frozen storage (Bhattacharya et al, 1988;Brewer & Harbers, 1991). However, the results for TL and CL suggest that frozen storage of beef patties caused little protein deterioration.…”
Section: Thawing and Cooking Lossescontrasting
confidence: 49%
See 1 more Smart Citation
“…Adding free amino acids and oxidized lipids to muscles containing added fat tended to increase lightness more than the other factors (Farouk & Swan, 1998). It also reduces lipid oxidation, which may result in lower L ⁎ values (Brewer & Harbers, 1992). The meat color values (a ⁎ value, b ⁎ value) of all samples were decreased at 7 days of cold storage with or without significant differences.…”
Section: Meat Surface Colormentioning
confidence: 95%
“…The hue angle of the meat product has been used to indicate the colour stability of fresh and processed meats (Brewer and Harbers, 1992). Leygonie et al (2012) reported that the CIE L*, a*, and Chroma values in the visual test were significantly decreased in the frozen/ thawed samples.…”
Section: Colourmentioning
confidence: 99%